Pengaruh Literasi Keuangan, Financial Technology, Risiko Keuangan, Sikap Keuangan dan Pendapatan Keuangan terhadap Pengelolaan Keuangan: Studi di Masyarakat Desa Kertasari Kecamatan Banjarharjo Kabupaten Brebes - Dian Agustiar; Heri Prabowo; C Tri Widiastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Financial problems are not only caused by low income, but financial difficulties can also arise if there are errors in financial management such as incorrect use of credit, and lack of financial planning. Therefore, financial literacy is needed for someone in managing their financial resources to be able to adjust to income and lifestyle in the modern era like today. The purpose of this study is to determine the effect of financial literacy, financial technology, financial risk, financial attitudes and financial income on financial management (study on the community of Kertasari Village, Banjarharjo District, Brebes Regency). This study uses a survey approach for its quantitative research design. The population used is the community in Kertasari Village with a population of 994 heads of families, having personal income, and being the head of the family. In determining the sample, the author uses the Slovin formula so that the number of samples obtained is 100 samples. The data analysis methods used are instrument testing, classical assumption testing, multiple linear regression testing, and hypothesis testing. The data obtained in this study were then processed using the IBM SPSS Statistics 23 program. The results of the study show that financial literacy has a positive and significant effect on financial management, financial technology has no effect on financial management, financial risk has a positive and significant effect on financial management, financial attitudes have a positive and significant effect on financial management, and financial income has a positive effect on financial management.